Unbound and Underground: Chile's Ergo Sun Project from the Dictatorship to the Digital Era - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results.
Keywords: dept.wll; faculty_collection; sabbatical_report

The Origins of Western Law from Athens to the Code Napoleon - Ecklund, John E. (Talbot Publishing, 2014)
Keywords: Europe; History; Law; Ancient; Law; Medieval; Law; dept.wll; faculty_collection; sabbatical_report

Modern Italian theater: (from Praga to Sciascia : text and context) - Vena, Michael (Xlibris LLC, 2014)
Keywords: 19th century; Theater; 20th century; Italy; Theater; dept.wll; faculty_collection

Sabbatical leave report: Fall 2014 - Cardone, Resha (2014)
Cardone wrote chapters of a book manuscript and submitted two related articles to peer reviewed journals. She also transcribed and edited a scholarly interview, presented portions of book project at conference and traveled to site of book topic for on-ground research. Accomplishments are different than outlined in original proposal. The report describes project issues and results. Book title is "Unbound and underground: Chile's Ergo Sun Project from the dictatorship to the digital era."
Keywords: dept.wll; faculty_collection; sabbatical_report

Meaning-based scoring: A systemic functional linguistics model for automated test tasks - Gleason, Jesse (Hispania-a Journal Devoted to the Teaching of Spanish and Portuguese, 2014)
Communicative approaches to language teaching that emphasize the importance of speaking (e.g., task-based language teaching) require innovative and evidence-based means of assessing oral language. Nonetheless, research has yet to produce an adequate assessment model for oral language (Chun 2006; Downey et al. 2008). Limited by automatic speech recognition (ASR) technology, which compares non-native speaker discourse to native-like discourse, most tests exclusively focus on accuracy while ignoring how examinees use language to make meaning. In order to offer stakeholders more trustworthy evidence of how examinees might use language in target language domains, a model anchored in systemic functional linguistics (SFL) is put forth. Specific examples are given of how SFL might be used to evaluate test task types, such as the story retell:three examinees' responses are contrasted using genre analysis (Derewianka 1990) and transitivity analysis (Ravelli 2000) in order to demonstrate elements in their linguistic profiles that ASR-based assessment would overlook. In so doing, implications are drawn regarding the potential of SFL models for enhancing automated scoring procedures by focusing on the meaning-form relations in the linguistic construction of narrative.
7 citations (Crossref) [2023-10-31] tex.eissn: 2153-6414 tex.unique-id: ISI:000345494100012
Keywords: Adult Spanish literacy alfabetización adulta de español; Automated language assessment evaluación automática del lenguaje; Discourse analysis análisis del discurso; Systemic functional linguistics lingüística sistémico-funcional; Transitivity analysis análisis de transitividad; dept.wll; peer-reviewed

Using big questions to apprentice students into language-rich classroom practices - Verplaetse, Lorrie Stoops (TESOL Quarterly, 2014)
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/067-055-821-290-826 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.wll

“It helps me get closer to their writing experience” Classroom ethnography and the role of technology in third-year FL courses - Gleason, Jesse (System, 2014)
Research has shown a disjunction between language instruction at the lower and upper levels of foreign language (FL) study. Whereas lower-division courses focus on grammatical patterns, upper-level courses focus on specific content. The third-year writing course is in a unique position to help learners prepare for the types of learning that they will encounter in more advanced language use contexts. Using grounded classroom ethnography, this multiple case study of two classrooms chronicles how a collaborative partnership between an instructor and an applied linguist facilitated the integration of two types of technology into a third-year Spanish writing course at a North American University. Technology was carefully chosen based on pedagogical considerations and teacher goals. Students in these courses included a mixture of heritage and FL Spanish learners with a mean age of 21 years. Findings included four ways that technology played a role in third-year Spanish language learning, including as: (a) a way to alleviate their workloads, (b) a motivator, (c) a way to improve the quality and quantity of feedback students received in the course, and in some cases (d) antagonistic to language learning. Implications of classroom ethnography for research on blended learning are drawn. Published by Elsevier Ltd.
4 citations (Crossref) [2023-10-31] Citation Key Alias: ISI:000345155800012, lens.org/016-859-492-698-057 tex.type: [object Object]
Keywords: Blended language learning; Discourse analysis; Ethnography; Language-content gap; Spanish; Teacher-researcher collaboration; Technology; Third-year FL courses; Writing; dept.wll